1980
DOI: 10.1161/01.res.47.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine and the carotid sinus baroreceptor reflex. Influence on capacitive and resistive properties of the total systemic vascular bed of the dog.

Abstract: properties of the total systemic vascular bed of the dog.Epinephrine and the carotid sinus baroreceptor reflex. Influence on capacitive and resistive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 20 publications
(20 reference statements)
6
31
0
Order By: Relevance
“…Because reflex blockade caused a 5.6 ml/kg increase in dog blood volume, there must have been a significant venous tone under the control conditions. The total response to 11.6 mI/kg (6±5.6) for reflex changes in vascular capacitance is similar to that reported by 23 from the baroreceptor reflex. Nonetheless reflex activity would appear to account for less than half of the total potential blood volume redistribution in response to peripheral blood flow changes.…”
Section: Discussionsupporting
confidence: 85%
“…Because reflex blockade caused a 5.6 ml/kg increase in dog blood volume, there must have been a significant venous tone under the control conditions. The total response to 11.6 mI/kg (6±5.6) for reflex changes in vascular capacitance is similar to that reported by 23 from the baroreceptor reflex. Nonetheless reflex activity would appear to account for less than half of the total potential blood volume redistribution in response to peripheral blood flow changes.…”
Section: Discussionsupporting
confidence: 85%
“…This agrees well with the average gain of 0.231 for carotid sinus reflex control of resistance reported here. In other experiments in which cardiac pumping and vascular capacity were also included, we have reported average carotid sinus gains to be 0.67 (Brunner et al, 1982) and 0.5 (Shoukas and Brunner, 1980). Several investigators have reported carotid and aortic reflex gains on resistance of isolated hindlimbs, rather than the resistance of the entire systemic vascular bed.…”
Section: Brunner Et Al/carotid and Aortic Reflex Interactionmentioning
confidence: 71%
“…The model also contains higher order carotid sinus and aortic arch terms to account for threshold and saturation behavior of arterial pressure and carotid sinus pressure (Martin et al, 1969;Shoukas and Brunner, 1980), and arterial pressure and aortic arch pressure (Angell- James and Daly, 1970a;Donald and Edis, 1971). A consequence of including these higher order terms is that the shape of the arterial pressure-receptor pressure relationship is sigmoidal.…”
Section: Statistical Model and Analysismentioning
confidence: 99%
“…SHOUKAS and SAGAWA (1973) reported that pressure change from 200 to 75 mmHg in the isolated carotid sinuses of vagotomized dogs resulted in a total blood mobilization of approximately 7.5 ml/kg from the total systemic vascular beds. By either decrease or increase in intrasinus pressure in a 50-125 mmHg range, the blood volume change in the total systemic vascular bed was 7.3 ml/kg (SHOUKAS and BRUNNER, 1980). HAINSWORTH and KARIM (1976) and KARIM et al (1978) demonstrated that by decreasing the isolated carotid sinus pressure from approximately 220 to 60 mmHg, the blood volume mobilized from the abdominal vascular bed in vagotomized dogs was approximately 5.0 ml/kg.…”
Section: Discussionmentioning
confidence: 98%